Lexicalized elements in khiva and urganch oghuz dialects - Mustafa (Uluslararası Türk Lehçe Araştırmaları Dergisi)
In Turkic, which has a well-developed word-making system, some words are made not only with affixes but also with the processed forms of lexical units. These lexical units may be words that complement the meaning or they may be in the position of auxiliary verbs. They can be processed as a result of various phonological processes such as elision, consonant assimilation and lose their characteristic of being lexical units and become elements that are used effectively in word construction. Lexicalization refers to the situation in which elements of a language enter the dictionary for various reasons. This situation is realized in various ways. This linguistic phenomenon, which can be seen in some sub-dialects and dialects of Turkic, is also seen in the dialects of Khiva and Urganch, which are among the Oghuz dialects spoken in Khwarezm. As far as can be determined, the lexicalization process takes place in these dialects through the fusion of the functioning words with the main element as a result of grammaticalization, the merger of auxiliary elements with the main element through becoming base, and the gerundium suffix -(X)p. The process of becoming base occurs when the auxiliary elements used after the main verb al- and the auxiliary verb et- are included in the main element as a result of various phonological processes. Additionally, in these dialects, the postpositions bilen and +din (< dey) are also functional words that are active in the lexicalization process. This study examines how lexicalized structures, which are handled in various ways in the historical and contemporary Oghuz varieties, are seen in Khiva and Urganch Oghuz dialects spoken in Khwarezm.